Biological diversity : frontiers in measurement and assessment - Magurran, Anne E., 1955-; McGill, Brian J. (Oxford biology, 2011)
Biological Diversity provides an up to date, authoritative review of the methods of measuring and assessing biological diversity, together with their application. The book's emphasis is on quantifying the variety, abundance, and occurrence of taxa, and on providing objective and clear guidance for both scientists and managers. This is a fast-moving field and one that is the focus of intense research interest. However the rapid development of new methods, the inconsistentand sometimes confusing application of old ones, and the lack of consensus in the literature about the best approach, means that there is a real need for a current synthesis. Biological Diversity covers fundamental measurement issues such as sampling, re-examines familiar diversity metrics (including species richness, diversity statistics, and estimates of spatial and temporal turnover), discusses species abundance distributions and how best to fit them, explores species occurrence and the spatial structure of biodiversity, and investigates alternative approaches used to assess trait, phylogenetic, and genetic diversity. The final section of the book turnsto a selection of contemporary challenges such as measuring microbial diversity, evaluating the impact of disturbance, assessing biodiversity in managed landscapes, measuring diversity in the imperfect fossil record, and using species density estimates in management and conservation.